A review of islanding detection techniques for renewable distributed generation systems - Khamis, Aziah (ELSEVIER, 2013)
Islanding detection of distributed generations(DGs)is one of the most important aspects of inter-connecting DGs to the distribution system.Islanding detection techniques can generally be classified as remote methods,which are associated with islanding detection on the utility sides,and local methods,which are associated with islanding detection on the DGside.This paper presents a survey of various islanding detection techniques and their advantages and disadvantages.The paper focused on islanding detection using a conventional and intelligent technique.A summary table that compares and contrasts the existing methods is also presented.